TESTING THE DIRECT AND INDIRECT EFFECT OF CAPITAL STRUCTURE ON THE STOCK PRICE OF THE SELECT INDIAN PUBLIC SECTOR BANKS - Ramaratnam, M.S.; Jayaraman, R. (International Journal of Research -GRANTHAALAYAH, 2017)
Market Value of Share of a company is determined by various factors. So many studies were conducted in finding the determinants of share price. Some of the studies found that Capital Structure is a determinant of the market price of the share and some of the studies found that Earning per Share is a determinant of the market price of the share. Even some studies proved that Capital Structure is also determining the Earning per Share. With this ideology an attempt was made in this study by using Structural equation modeling to see how for the Capital Structure of the firm has got a direct and indirect effect over the Market value of share. Debt to Total Assets, Equity to Total Assets, Coverage Ratio, Earning per share and Market price of share of eleven Indian public sector banks were taken for the study for five years from March 2013 to March 2017.